Significações da violência urbana: resgatando um espaço roubado - Silva, Letícia Francisca Alves da (2008)
The actual study had the objective of investigating how the workers involved in combat of violence give signification to this phenomenous in working situations and what they feel about the violence they deal with in the working time. Using the qualitative perspective techniques, utilizating the automatic discursive analyzes of Michel Pêcheux and Herrmann interpretation, the study was developed with the participation of 6 police officers, 3 psychologists and a justice promoter, all of them actuating in the public service from Triangle Mineiro cities. After the transcription, the reading and interviews interpretations, it could be notice that these workers feel forsaken by their original institutions and by other ones that are so responsible by the social control. These institutions are omitted in some occasions and in others they are extremely repressive. All these facts make them promote embarrassment and fear in the function normative development. Furthermore, the violence combatants agree that even the society seams to have resigned to the order importance e are hostile with the control function that these combatants develop. Isolation, violence and time urgency are mentioned as the social relations modulators nowadays, ruled mainly by the capital order. It could be notice that culture and institutional reforms were suggested to violence problems by these workers cause they think that several values as Education and Order must be recuperated by several institutional dispositives, including police and family. So, it could be seen that was important to offer a signification moment to the violence combatants because it seems to be the first step to put in practice their own suggestions a culture and institutional reformation. In an effort to make weaker the embarrassing products of violence, it can be pointed that other expression spaces can be offered mainly inside their own institution.